2020
DOI: 10.53420/apjcs.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Beliefs on Philippine Educational and Curriculum Practices: What Educators Can Learn from Them

Abstract: Parents are part of the school community. However, schools have neglected to tap parents’ opinions and perceptions of new programs for implementation (Ornstein & Hunkins, 2009). Upon this background, Dodd (1988) conducted her research to gain a better understanding of the curriculum and practices parents favored, including their underlying beliefs about teaching and learning high school English. This study replicated Dodd’s (1998) research to explore the understanding of educational practices that Filipino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies showed that less literate parents and those from a lower socioeconomic status prefer a more traditional approach to learning and direct teaching activities. On the other hand, parents who have higher literacy and belong to a higher socioeconomic status favored a less structured and broader range of activities for literacy (Beltran-Almazan et al, 2020).. Thus, educated parents become good facilitators to their children.…”
Section: Barriers That Inhibit School-home Collaborative Efforts For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that less literate parents and those from a lower socioeconomic status prefer a more traditional approach to learning and direct teaching activities. On the other hand, parents who have higher literacy and belong to a higher socioeconomic status favored a less structured and broader range of activities for literacy (Beltran-Almazan et al, 2020).. Thus, educated parents become good facilitators to their children.…”
Section: Barriers That Inhibit School-home Collaborative Efforts For ...mentioning
confidence: 99%
“…The study of Beltran-Almazan et al (2020) showed that parents' views on literacy and education play a vital role in home-school collaboration. These views are shaped by two demographic factors: parents' level of education and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%